2014
DOI: 10.4103/0972-0707.131802
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro evaluation of effect of eugenol exposure time on the shear bond strength of two-step and one-step self-etching adhesives to dentin

Abstract: Objectives:To evaluate the effect of the eugenol exposure time of an eugenol-based provisional restorative material on the shear bond strength of two-step and one-step self-etching adhesives to dentin, at three different time intervals of 24 h, 7 days, and 14 days.Materials and Methods:Forty extracted human posterior teeth were sectioned mesiodistally to obtain two halves and the resulting 80 halves were randomly assigned into four groups of 20 specimens each (Group-I, -II, -III, and -IV). Cavities of specifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…suggested that ZOE affects the adhesive properties of resins either by changing the wettability and reactivity of the dentin or by interaction of the remnants of the ZOE material with the setting mechanism of resin composites. [ 4 5 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…suggested that ZOE affects the adhesive properties of resins either by changing the wettability and reactivity of the dentin or by interaction of the remnants of the ZOE material with the setting mechanism of resin composites. [ 4 5 ]…”
Section: Discussionmentioning
confidence: 99%
“…also fabricated restorations in the form of discs with 2 mm diameter and 3 mm height. [ 4 ] Saraç et al . used 4 mm × 4 mm × 1 mm acrylic resin plates as temporary restoration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intensity of the interaction of SE adhesive systems with dentin was mostly dependent on the acidity and aggressiveness of the primer used. [ 17 ] SE adhesives have been classified based on their ability to penetrate smear layers and depth of demineralization as ultra-mild (pH >2.5), mild (pH ~2), moderately strong (pH 1-2), and strong (pH ≤1). The manufacturer of dyad flow has declared that it has a pH of 1.9, and One Coat 7.0 (Coltene Whaledent, Switzerland), a mild SE adhesive, has a reported pH of 2.0.…”
Section: Discussionmentioning
confidence: 99%